PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018) - Nisa, Aminun; Syaifuddin, Dedy Takdir; Budi, Nuryamin; Saleh, Salma; Amstrong, Valentinus (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims to examine the effect of investment decisions, funding decisions, profitability and dividend policy on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. The independent variables used are investment decisions proxied by price earning ratio (PER), funding decisions proxied by debt to equity ratio (DER) and debt to assets ratio (DAR), profitability as proxied by return on assets (ROA), return on equity (ROE) and net profit margin (NPM) and dividend policy as proxied by dividend payout ratio (DPR), and dividend yield. The dependent variable used is the firm value which is proxied by the price book value (PBV). The population of this study are manufacturing companies listed on the Indonesia Stock Exchange. By using purposive sampling method, 26 companies were taken as samples. The analytical technique used is Structural Equation Modeling (SEM) with the help of the SmartPLS3 program. The results showed that investment decisions (PER), funding decisions (DER, DAR), and profitability (ROA, ROE and NPM) had a positive and significant effect on firm value (PBV). This means that increasing investment decisions (PER), funding decisions (DER, DAR), and profitability (ROA, ROE and NPM) can increase firm value (PBV). On the other hand, dividend policy has a negative but not significant effect. This means that increasing or decreasing dividend policy does not affect firm value.